2004
DOI: 10.2174/0929867043456089
|View full text |Cite
|
Sign up to set email alerts
|

Atypical Antipsychotics: Pharmacokinetics, Therapeutic Drug Monitoring and Pharmacological Interactions

Abstract: The development of new "atypical" antipsychotic agents, which are safer than classical neuroleptics and also active against the negative symptoms and neurocognitive deficits caused by the illness, has produced a significant advancement in the treatment of schizophrenia. The atypical (or "second generation") antipsychotics have several therapeutical properties in common, however they can significantly differ with regard to clinical potency and side effects. The main features regarding pharmacodynamics, pharmaco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
67
0
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(69 citation statements)
references
References 0 publications
0
67
0
2
Order By: Relevance
“…1), was developed as a neuroleptic agent, and has been clinically used with relatively few extra-pyramidal side effects. 1,2 Despite the clinical usefulness of zotepine, very few studies have focused on a method for quantifying zotepine, except for an early study by Noda et al 3 The only methods for zotepine determination reported to date involve a complicated and time-consuming extraction procedure, e.g. a gas-liquid chromatographic (GC) method consisting of three liquid-liquid extractions using 1 mL biological samples and the GC-MS method, requiring solid-phase extraction and an evaporation process.…”
Section: Introductionmentioning
confidence: 99%
“…1), was developed as a neuroleptic agent, and has been clinically used with relatively few extra-pyramidal side effects. 1,2 Despite the clinical usefulness of zotepine, very few studies have focused on a method for quantifying zotepine, except for an early study by Noda et al 3 The only methods for zotepine determination reported to date involve a complicated and time-consuming extraction procedure, e.g. a gas-liquid chromatographic (GC) method consisting of three liquid-liquid extractions using 1 mL biological samples and the GC-MS method, requiring solid-phase extraction and an evaporation process.…”
Section: Introductionmentioning
confidence: 99%
“…The subjects prescribed CPZE2 had significantly better outcomes on days three and seven follow-up than subjects prescribed CPZE1. Even though, from the findings, CPZE doses ≤ 300 mg may be the minimal effective doses in patients (21), it appears that this dose is suboptimal and caution should be taken when prescribing doses < 300 mg to male cannabis users with a diagnosis of schizophrenia or schizophreniform disorder. Clinical assessment of the subjects further underscored this finding as most of the subjects who received > 300 mg CPZE attained clinical improvement by day seven compared to only two of eight subjects showing clinical improvement with the lower CPZE dose.…”
Section: Discussionmentioning
confidence: 99%
“…Diphenhydramine and quetiapine have relatively short durations of effect [12]. However, in overdose the relatively predictable pharmacokinetics and pharmacodynamics change, making estimates of duration of action difficult [13]. This is particularly applicable when one considers the frequent implication of quetiapine in our patients, which in standard doses has modest muscarinic receptor binding [14].…”
Section: Discussionmentioning
confidence: 99%